Methoxy polyethylene glycol modification promotes adipogenesis by inducing the production of regulatory T cells in xenogeneic acellular adipose matrix. (September 2021) - Liu, Kaiyang; He, Yunfan; Yao, Yao; Zhang, Yuchen; Cai, Zihan; Ru, Jiangjiang; Zhang, Xiangdong; Jin, Xiaoxuan; Xu, Mimi; Li, Yibao; Ma, Qizhuan; Gao, Jianhua; et al.
Abstract: Acellular adipose matrix (AAM) has emerged as an important biomaterial for adipose tissue regeneration. Current decellularization methods damage the bioactive components of the extracellular matrix (ECM), and the residual immunogenic antigens may induce adverse immune responses. Here, we adopted a modified decellularization method which can protect more bioactive components with less immune reaction by methoxy polyethylene glycol (mPEG). Then, we determined the adipogenic mechanisms of mPEG-modified AAM after xenogeneic transplantation. AAM transplantation caused significantly lesser adipogenesis in the wild-type group than in the immune-deficient group. The mPEG-modified AAM showed significantly lower immunogenicity and higher adipogenesis than the AAM alone after xenogeneic transplantation. Furthermore, mPEG modification increased regulatory T (Treg) cell numbers in the AAM grafts, which in turn enhanced the M2/M1 macrophage ratio by secreting IL-10, IL-13, and TGF-β1. These findings suggest that mPEG modification effectively reduces the immunogenicity of xenogeneic AAM and promotes adipogenesis in the AAM grafts. Hence, mPEG-modified AAM can serve as an ideal biomaterial for xenogeneic adipose tissue engineering. Graphical abstract: Image 1